High level of infection by toxoplasma gondii in pigs slaughtered in the city of são luís, maranhão - Silva, Ellainy Maria Conceição; Dos Santos Sousa, Pablo; De Carvalho, Scarleth Kevia Gomes Silva; Marques, Ingrid Carolinne Lopes; Costa, Francisco Borges; Da Costa, Andrea Pereira; Dos Santos, Larissa Sarmento; Do Socorro Costa Oliveira Braga, Maria; Abreu-Silva, Ana Lúcia; Machado, Rosangela Zacarias [UNESP]; De Carvalho Neta, Alcina Vieira (FapUNIFESP (SciELO), 2021)
The article presents an exploratory, descriptive study on Bad News Communication skills (CMN) of medical interns. The student’s perception was on learning for the CMN was investigated with a cross-sectional design and a mixed approach. A questionnaire was applied, 176 participants were obtained, and a focus group was held with 12 students. The data were analyzed through the calculation of means and standard deviations for quantitative variables and the focus group reports were subjected to Content Analysis. It was observed that in the group that had training, compared to the one who did not, ocurred twice frequency with more skill for CMN. In the CMN’s management, it was considered harder to be “honest without taking away hope” (69%) and “to deal with the patient’s emotion” (59%). 99.4% knew the SPIKES protocol, of which 41.5% considered the expression of emotions as its most difficult stage. Communication and handling of emotions were pointed out as the main difficulties in the doctorpatient relationship, with deficits in the teaching of CMN. It was found that CMN is not limited to the technical issue, but it involves attitudes that need to be addressed with different methodologies, as well as the implementation of educational policies in the medical field, especially given the demands that emerges with the covid-19 pandemic.
Alto nível de infecção por Toxoplasma gondii em suínos abatidos na cidade de São Luís, Maranhão
Keywords: Communication; Education Medical Undergraduate; Medical Education; Physician-Patient Relations